Research on the Evaluation Model of Athletes Youth Mental Health Education in the context of Positive Psychology - Tian Zhang; Zhanbiao Shi, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Athletes meet their satisfaction level instead of being parallel in the psychological process. This study portrait that Mental Health is impacted by the self-determination and motivation level of athletes. It was found that Mental Issues is mediated by the coach and athletes’ relationship. Athletes might face problems such as mental stress, heavy burden, and psychological demands of training, which could create a significant impact on the Mental Health of athletes. Internal and External Stimulus is the type of self-motivation, and it is concerned with participating an athlete in an activity for the sake of amusement, interest, and satisfaction. This paper has two IV; Self-Determination and Motivation, and one DV (Mental Health). Whereas, the Coach-Athlete Relationship mediates the association between IV and DV. The data was collected from male and female athletes in between 18-35 age groups. The participants were selected randomly from various sport’s training center. The selected data was collected and analyzed AMOS 26v. The research model is based upon self-determination theory. The results supported the hypothesis of study, and showed a significant fitness in model.